2014
DOI: 10.1083/jcb.201404109
|View full text |Cite
|
Sign up to set email alerts
|

Mouse BRWD1 is critical for spermatid postmeiotic transcription and female meiotic chromosome stability

Abstract: Exhibiting sexually dimorphic roles in mice, BRWD1 is essential for proper meiotic chromosome condensation and telomere structure during oogenesis and for haploid-specific gene transcription during postmeiotic sperm differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 73 publications
(123 reference statements)
1
34
0
Order By: Relevance
“…However, we (data not shown) and others [18] detected BRD4 solely in spermatogonia. Recently, it has been shown that the dual bromodomain-containing protein BRWD1 is involved in transcription of about 300 genes, most of which are activated in spermatids [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, we (data not shown) and others [18] detected BRD4 solely in spermatogonia. Recently, it has been shown that the dual bromodomain-containing protein BRWD1 is involved in transcription of about 300 genes, most of which are activated in spermatids [59].…”
Section: Discussionmentioning
confidence: 99%
“…Modified histones are recognized by 'reader' proteins, which are often components of chromatin-remodeling complexes that are involved in the histone-to-protamine transition. For example, bromodomain-containing proteins, such as BRDT and BRWD1, bind to hyperacetylated histones before histone removal from the chromatin, and mice lacking BRWD1 or expressing mutant BRDT are sterile due to impaired spermiogenesis (Pattabiraman et al, 2015;Shang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the factors that drive expression of the TSSK genes during spermatogenesis, with the exception of TSSK6 (also known as small serine/threonine kinase, SSTK), which is highly dependent on BRWD1 (Pattabiraman et al, 2015). Heat shock protein 90 (HSP90) is essential for the stability of all TSSKs and for catalytic activation of TSSK2 and TSSK4 (Jha et al, 2013(Jha et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Spermiogenesis is a complex postmeiotic process during which gross morphological, biochemical, and physiological modifications of round spermatids create the mature spermatozoa (Steger, ). During spermiogenesis, the round spermatids elongate, acquire an acrosomal cap, develop a tail, and extrude most of their cytoplasm as residual bodies; while their nuclei undergo extensive condensation as the histones are replaced by protamines (Pattabiraman et al, ). These protamines tightly pack the spermatid DNA for stringent, temporal regulation of stage‐specific gene expression, which is required for the differentiation of round spermatids into mature sperm (Steger, ).…”
Section: Introductionmentioning
confidence: 99%